Effect of foulants on arsenic rejection via polyacrylonitrile ultrafiltration (UF) membrane - Agarwal, Gopal P.; Karan, Raj; Bharti, Sachin; Kumar, Hemant; Jhunjhunwala, Sumit; Sreekrishnan, T. R.; Kharul, Ulhas K. (Desalination, 2013)
Arsenic rejection via modified polyacrylonitrile ultrafiltration (UF) membrane was found to be very high, however, the presence of commonly found foulants in arsenic solution affected membrane performance. The effect of commonly found foulants, such as ovalbumin, humic acid and egg white on arsenic rejection were studied. Experiments indicated that the As(V) rejection was affected by the total quantity of proteins and not the variety of proteins present in a solution. As(V) rejection was found to decrease with increasing proteins while fouling was found to increase from 25% for 0.1 mg/ml to 33% for 0.5 mg/ml egg white. The As(V) rejection was found to decrease with increasing concentration of humic acid for PAN membranes. Fouling studies showed that humic acid was a lesser foulant in comparison to egg white. However a combination of the two foulants led to a decrease in the overall fouling. pH was also found to be a very important factor for egg white dissolution and As(V) rejection. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Arsenic rejection; Egg white; Humic acid; Ovalbumin; Polyacrylonitrile; Ultrafiltration

Dual inhibition of AXL and MER kinase: scope for lung and breast cancer therapeutics - Sathe, Balaji Dashrath; Kumari, Pratibha; Kumar, Hemant; Mane, Madhav Shivaji; Mudududdla, Ramesh; Baell, Jonathan; Kumar, Roshan; Singh, Shareen; Pawar, D. K.; Kommi, Damodara N.; Bushi, Ganesh; Pathak, Prateek; et al. (Bioorganic Chemistry, 2025)
Cancer cells use multiple survival pathways for continuous proliferation, survival, and growth. Recent anticancer drug discovery commonly focuses on a single target that maintains key cancer cell survival mechanisms, where typically, this is a cellular enzyme that inhibits DNA replication, inducing cell damage and apoptosis. Since drugs that act on a single target may be more susceptible to the development of resistance, the search for polypharmacotherapeutics is becoming increasingly popular to defeat drug-resistant cancer cells. Receptor tyrosine kinases (RTKs) family members, AXL and MER, have been identified as important cancer targets and found to be overexpressed and associated with various forms of cancers, such as lung and breast cancers. This review has focused on the dual inhibition of AXL and MER kinases as a strategy for treating lung and breast cancer. The roles of these two kinases in non-small cell lung cancer (NSCLC) are such that dual inhibition would be therapeutically complementary, with MER inhibition more fully blocking tumor growth while AXL inhibition encourages chemosensitivity. Hence, treatment strategies targeting both of these RTKs may be more effective and beneficial than singly targeted agents, and a dual AXL/MER inhibitor is a potential therapy for NSCLC along with breast cancer. This review highlights the preclinical and clinical development of dual AXL and MER kinase inhibitors as lung and breast cancer treatments and the prospects for their future progression.
Keywords: AXL; Breast cancer; Cancer therapy; MER; Multi-kinase inhibitors; NSCLC targeted therapy